Understanding the moderating role of chronotypes for online mobile gaming in-app purchase intention - Beenish Tariq; Thurasamy Ramayah; Mark D. Griffiths; Antonio Ariza-Montes; Heesup Han (European Research on Management and Business Economics)
In the highly dynamic and fast growing online mobile gaming industry, revenue streams are the most important for the game developers. One of the significant ways to generate revenues is to boost the in-app purchases by gamers. Using Stimulus-Organism-Response (SOR) framework, the present study modelled addiction, loyalty and in-app purchases with chronotypes (a biological disposition) as a moderator. The study posited that loyalty is one of the significant mediators to convert addiction into in-app purchases. For the present study, 345 university students completed a survey, and the data were analyzed via SmartPLS using multigroup analysis. The moderation of chronotypes (a biological disposition) and mediation of loyalty for in-app purchase intention were tested and supported by the results. The study suggested that evening type individuals had a higher tendency to be loyal towards online mobile gaming compared to morning type individuals. Moreover, evening type individuals had higher inclination toward in-app purchase intention compared to morning type individuals. Loyalty functioned as a mediator between addiction and in-app purchase intention. The present study is one of the first to investigate the role of chronotypes as moderator and loyalty as a mediator for online mobile gaming in-app purchase intention utilizing the SOR framework. From a practitioners’ perspective, the present study highlighted a loyal segment of gamers who is more inclined to make in-app purchases. In addition, it highlights a dilemma for gaming operators to balance revenue generation with the well-being of its clientele.